INTERNATIONAL LEGAL REGULATION OF PRINCIPLES IN THE FIELD OF CLIMATE PROTECTION - Ахмет , Ғалымжан Бауржанұлы; Bekezhanov, Dauren; Сериев, Болат Абдулдаевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article carried out comprehensive theoretical studies of foreign legislation in Environmental Protection. Principles in the field of climate protection are of great importance in the world. This is because climate change is contributing to an increase in the incidence of natural disasters. Environmental protection measures are provided for by the United Nations Framework Convention on climate change, the Paris agreement on climate change, the United Nations Framework Convention on climate change, the United Nations Environment and Development Conference. In developed countries, special principles have been introduced in the Prevention of environmental conditions, environmental safety and climate disasters based on international legal acts. The new principles of climate protection are aimed at preventing damage to the environment, preserving the environment, and using natural resources more efficiently. The legal principles of climate protection contribute to ensuring environmental safety, preventing harmful effects on natural resources, improving the quality of life of people through careful use of Natural Resources and other natural resources. The Paris Agreement is the first treaty ratified in the world, adopted by all heads of state at the United Nations conference on climate change. The main goal of the Paris Agreement is considered to be the management of the environment by developing states through the effective organization of several measures aimed at combating climate change. By conducting a legal analysis of various solutions of international organizations, the authors proposed important and effective principles that contribute to solving climate change problems.